Taxing Issues with Privatization : A Checklist - Mintz, Jack M.; Chen, Duanjie; Zorotheos, Evangelia (World Bank, Washington, DC, 2014)
Privatization has been a popular strategy for improving efficiency in both market and transition economies. The literature on privatization includes broad discussions of pricing techniques but overlooks tax issues. In reality, a state-owned company loses its privilege of paying no taxes once it is privatized. This change in tax status would certainly complicate the financial transaction of a newly privatized company, affect industry-wide economic efficiency, and change the revenue pattern of governments. Using Ontario Hydro and the Canadian tax regime as examples, the authors provide policymakers with a checklist on tax issues under privatization. Their main observations: 1) The tax status of the company to be privatized must be considered in analyzing the firm's financial transition. 2) The economic efficiency targeted by privatization may depend partly on the tax regime for a particular industry. 3) Privatization affects government revenue through the revenue-sharing structure determined by intergovernmental fiscal relationships and cross-border tax arrangements. Time is a factor in tax and transition issues. At the time of privatization, for example, how are assets to be valued for calculating capital gains and cost deductions, for tax purposes? Are the assets transferred to the new owners at fair market value, book value, or at cost, for tax purposes? How should heavy debt loads be treated? Ontario Hydro will not be privatized but it will become taxable. How the taxes will be paid will depend on how the transition is treated. Tax policy will be a key determinant of the industry's future development.